SERIES OF ARGUMENTS ON PROCESSES OF CRITIQUES TO MATHEMATICAL PROBLEMS - Nugroho, Bayu; Nusantara, Toto; As'ari, Abdur Rahman; Sisworo, Sisworo (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
This study was initially based on the researcher?s interest in a case found in students as they responded mathematical problems provided in the form of critiques to a problem. The study aimed to explore the students? arguments to describe the students? thinking processes while they are giving critiques to a mathematical problem. The study was qualitative research in a case study involving one student as a subject of research.  The finding showed that the students used 4 series of arguments as the main reason to give critiques to the given problem. The critiques were delivered due to several factors consisting of; (1) the students? inability to discover appropriate strategies to deal with the given problems; (2) the personal experiences kept in a Long Term Memory, and (3) the fallacy on reasoning.